Estimating the potential effects of climate change on GDP in the agriculture sector by countries in the ASEAN region - Vannasinh Souvannasouk; Wichuda Singkam; Nirote Sinnarong; Ke Nunthasen; Waraporn Nunthasen; Anupong Wongchai (Maejo International Journal of Energy and Environmental Communication, 2021)
This study estimates the potential effects of climate change on GDP in the agriculture sector in the ASEAN region based on historic data from 1995-2018. An econometric panel model is applied to examine the impact of the changing climatic and non-climate variables AGDP. The empirical estimation results show that some significant and insignificant. Based on estimation results, if the policymaker is concerned about climate change actions, it helps more comprehensive risk decision-making, and policy exertions should be concentrated toward climate change to the total gross domestic product in the ASEAN region. Under projections of the future climate change, the simulation results reveal that the substantial change in GDP in agriculture in the ASEAN region arises due to the fluctuation of temperature and precipitation. For instance, GDP in the agriculture sector would be decreased by 0.27% to 0.90% in response to different scenarios over the century. Therefore, it is necessary to take immediate adaptive actions appropriately to mitigate the decrease in GDP in the agriculture sector in the ASEAN region.